Inclusion of leakage into life cycle management of products involving plastic as a material choice - Chitaka, Takunda Yeukai (Department of Chemical Engineering, 2021)
The accumulation of plastic waste in the natural environment has been a major environmental concern for many decades. However, the environmental impacts associated with leakage are not taken into consideration under current life-cycle based approaches, despite packaging being a major application area of life cycle assessment. Furthermore, there is limited quantitative information on the leakage propensities and rates of different products. This presents a critical limitation during the life cycle management (LCM) of products destined for regions where they are likely to be dumped or littered. This thesis investigates the feasibility and influence of using product specific leakage rates as a proxy indicator for potential marine environmental impacts, to inform the life cycle management of products in which plastic is a material choice. In particular, it explores whether a realistic understanding of leakage rates, differentiated by major use, may facilitate the development of effective interventions to mitigate the growing problem of marine plastic pollution. This entails the quantification of leakage rates for selected plastic items identified as highly prone to leakage based on a series of beach surveys. The potential influence of providing such specific knowledge is investigated via the exploration of current LCM practices for plastic products employed by key value-chain actors in the plastics industry. In addition, the life cycle management of three key items identified as problematic (straws, cotton bud sticks and beverage bottle lids) is explored via a case study approach. Beach accumulation surveys are often used to estimate plastic flows into the marine environment. Thus, two series of beach surveys were conducted across five beaches with varying catchment area characteristics in Cape Town, over two periods in 2017 and 2018 – 2019 respectively. Daily accumulation rates varied across all sites ranging from 38 – 2962 items.day-1 .100m-1 during the first sampling period and 305 – 2082 items.day-1 .100m-1 during the second. Plastic was the major contributor accounting for 85.6 – 98.9% of all items by count. Despite the variations in litter accumulation rates and composition, there was significant commonality in the items which were identified as major contributors. The top 12 most prevalent and abundant identifiable plastic items accounted for 43 – 66% during the first sampling period, and 41 – 73% during the second. Ten of these items were prevalent during both periods, eight of which were associated with food consumed on-the-go, including beverage bottle lids, polystyrene food containers, single sweet wrappers, snack packets and straws. This indicates that the high litterability of these items was consistent across catchment areas and sampling periods. Furthermore, when ratioed to waste generation, items found to be major contributors were found to have significantly higher leakage rates in comparison to less prevalent items. The increasing concern surrounding plastic pollution has pressured value-chain actors to review their approaches to the life cycle management of plastic products. This has led to the development of strategies focussed on plastic packaging which were not commonplace across all companies. However, these strategies are not necessarily aimed at mitigating plastic pollution but are more broadly concerned with sustainable product design, emphasising design for recycling and supporting recycling activities at end-of-life as part of their extended producer responsibility. Thus, the extent to which these strategies address plastic pollution is limited. Furthermore, value-chain actors reported varied approaches to product prioritisation for intervention which are often not grounded in empirical evidence but instead based on anecdotes and limited logic. This may be attributed to a lack of reliable product-specific information surrounding plastic pollution. Such approaches have the potential to prioritise products ii which are not major contributors to marine pollution in lieu of those that are. Interventions targeted towards products that were identified as prone to leakage, including straws and cotton bud sticks, were catalysed by consumer pressure and societal expectations at large. Ultimately, this thesis demonstrates the need for product-specific knowledge on leakage to facilitate responsible and effective life cycle management of products involving plastic as a material choice. Furthermore, it has demonstrated the feasibility of providing such information through the use of leakage rates. Leakage rates have the potential to play an important role in product life cycle management, allowing for the identification of products which are highly prone to leakage into the environment. Thus, their integration into LCM practice has the potential to facilitate the development of targeted strategies to address plastic pollution.